Chemotherapy and targeted therapies for meningiomas: what is the evidence?. Issue 6 (December 2021) - Graillon, Thomas; Tabouret, Emeline; Chinot, Olivier
Abstract : Purpose of review: Although most meningiomas are slow growing tumors mainly controlled by surgery with or without radiotherapy, aggressive meningiomas that fail these conventional treatments constitute a rare situation, a therapeutic challenge and an unmet need in neuro-oncology. Recent finding: Mutational landscape in recurrent high-grade meningiomas includes mainly NF2 mutation or 22q chromosomal deletion, whereas telomerase reverse transcriptase promoter, BAP-1 and CDK2NA mutations were also found in aggressive meningiomas. Pi3K-Akt-mTOR pathway is currently the most relevant intracellular signaling pathway target in meningiomas with preliminary clinical activity observed. Assessment of drug activity with progression free survival rate at 6 months is challenging in regard to meningioma growth rate heterogeneity, so that 3-dimensional growth rate before and during treatment could be considered in the future to selected new active drugs. Summary: Despite a low evidence level, some systemic therapies may be considered for patients with recurrent meningioma not amenable to further surgery or radiotherapy. In recurrent high-grade meningioma, everolimus-octreotide combination, bevacizumab, sunitinib and peptide receptor radionuclide therapy exhibit a signal of activity that may justify their clinical use. Despite a lack of clear signal of activity to date, immunotherapy may offer new perspectives in the treatment of these refractory tumors.